Performance comparison of chip processing receivers for DS/CDMA systems with very fast fading - Ho, P.; Jae Hyung Kim (1997 IEEE International Conference on Communications, 1997)
This paper is concerned with the subject of coding and detection for DS/CDMA systems operating under very fast Rayleigh fading. Specifically, we compare the performance of various chip level detectors, including the chip level pilot-assisted coherent detector, chip level differential detector, chip level non-coherent detector, and the chip level maximum likelihood detector. The true union bounds on the bit error rate of these detectors were computed, with the fade rate, coding rate, and the spreading factor as parameters. It was found that these detectors are very robust against fast fading. A reasonable level of data integrity can be maintained even if the fade rate is as large as 10% of the chip rate. Among the various detectors, the pilot-aided chip level coherent detector has the best performance while the chip level differential detector is the worst. Surprisingly enough, the optimal pilot-aided detector, under the assumption of ideal interleaving, uses a transmission format that consists of an alternating pattern of pilot and coded data symbols. It was also found that chip level differential detection performs better than its symbol level counterpart only when the fade rate exceeds 6% of the chip rate.